Lipiodol embolization for chylous leak complication post robotic-assisted para-aortic lymph node resection - Perisamy, Rajeev Shamsuddin; Rusli, Rusli Zaim; Kamis, Mohd Fandi; Tharek, Anas; Soo, Tze Hui (Elsevier, 2024)
Thoracic or abdominal chylous leakage, a rare complication of lymph node removal procedures, can lead to the accumulation of lymph fluid within the abdominal cavity, resulting in chylous ascites, abdominal distension, discomfort, and an increased risk of infection. Lipiodol lymphangiography, a diagnostic procedure utilizing a unique contrast agent, serves to identify the site and cause of chylous leaks. Furthermore, it functions as a therapeutic tool by injecting Lipiodol into the affected lymphatic vessel. By employing this diagnostic procedure, successful closure of the leak can be achieved. We present a case where a chylous leak was effectively treated with Lipiodol injection following the robotic-assisted removal of metastatic lymph nodes surgery.